VERTICAL PROFILE OF POLYCYCLIC AROMATIC HYDROCARBONS IN A SEDIMENT CORE FROM A RESERVOIR IN OSAKA CITY - Ishitake M.; Yoshikawa S.; Moriwaki H.; Katahira K.; Yamamoto O.; Tsuruho K.; Yamazaki H. (My University, 2007)
Concentrations of polycyclic aromatic hydrocarbons (PAHs) were measured in a dated sediment core from a reservoir at Osaka City, Southwest Japan. The sediment core consisted of deposits collected over a period of almost 70 years whose PAH content would serve as a historical record of atmospheric environment at Osaka City. Total PAH concentrations varied from 4.2 to 26 mg kg−1 dry wt, and peaked in the 1940s, reflecting the occurrence of a large fire due to air attacks during World War II. The results indicated that warfare had the largest impact on atmospheric environment in Osaka City. Total PAH concentrations decreased in the post-war period except for a small peak. In the 1950s, there was a downward trend from the 1970s to the present. These trends can be ascribed to the growth of industrial activities and the regulation of atmospheric pollutant emissions, respectively.
Keywords: CLIMATOLOGY; OSAKA CITY; POLYCYCLIC AROMATIC HYDROCARBONS; RESERVOIR SEDIMENT; WORLD WAR II